Praktik Sosial Catcalling Pada Remaja Di Kecamatan Cikeusal Kab. Serang-Banten - Indriayni Indriyani; Rizki Setiawan; Septi Kuntari (Universitas Lambung Mangkurat, 2024)
This research aims to determine the social practice of catcalling in Cikeusal District. Catcalling according to Chhun (2011) identifies catcalling as the use of indecent words, verbal expressions and also non-verbal expressions which occur in public places, for example on roads, on sidewalks and bus stops. Verbally, catcalling in usually done through whistling or comments about a womens appearance. Non-verbal expressions also include glances of physical gestures that act to provide an assessment of a woman’s appearance. The method in this research uses a qualitative research method with a descrptive approach, meaning that the research results are formulated after all the data has been analyzed. In simple terms, it can stated that qualitative research is examining informants as research subjects in their daily living environment. The results of this research in clude the social practice of catcalling in cikeusal village, the meaning of catcalling in society.